The Magical World of Disney: building relationships with clients from the brand personality - Gabriela Nobre Dias; Gisela Demo; Fernanda Scussel (Tourism & Management Studies)
The purpose of this study is to evaluate the relationship between brand personality and customer relationship perception in the Tourism and Hospitality Industry. We performed a survey with 283 Brazilian visitors of Disney parks, using Structural Equation Modeling. Brand personality, the second-order factor, was formed by first-order factors (Credibility, Joy, Sophistication, Audacity and Sensitivity), all of them with positive effects on customer relationship perception. The prediction was 29%, considered a great effect. Hence, we confirm the relation between brand personality and relationship perception and the Credibility dimension as the main driver of long-term relationships in the T&H sector. Our discussion contributes to the body of knowledge of relationship marketing and branding, especially in identifying the nature of the relationship between these marketing variables. Research on brand management can benefit from our results since they put light into the interaction between brand and customers, and the main aspects sustaining these interactions.